The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/v12010046
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis of the Brainstem in EV71- and CVA16-Infected Gerbils

Abstract: Enterovirus 71 (EV71) and coxsackievirus A16 (CVA16) are the two most important pathogens of hand, foot, and mouth disease (HFMD). However, the neuropathogenesis of EV71 and CVA16 has not been elucidated. In our previous study, we established gerbils as a useful model for both EV71 and CVA16 infection. In this work, we used RNA-seq technology to analyze the global gene expression of the brainstem of EV71- and CVA16-infected gerbils. We found that 3434 genes were upregulated while 916 genes were downregulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, inhibition of C5aR1 was reportedly shown to confer a considerable level of protection in brain disorders involving neuroinflammatory responses and blood brain barrier disruption (Jacob and Alexander 2014 ). Jiang et al ( 2019 ) reported complement overactivation in macrophages, which resulted in immunopathology with overexpression of caspase-1 and IL-1β levels in the serum, and subsequently, pyroptosis of these cells in a mouse model of MERS-CoV infection (Jiang et al 2019 ). Notwithstanding, treatment with anti-C5aR1 antibody effectively suppressed the expression of caspase-1 and IL-1β, to abrogate the immunopathology and pyroptosis of the macrophages, suggesting that C5a/C5aR1 signalling pathway constitutes a potential target for the treatment of SARS-CoV-2 infection (Jiang et al 2019 ).…”
Section: Neuroimmune Dysregulation By Sars-cov-2 Neuroinvasionmentioning
confidence: 99%
“…Interestingly, inhibition of C5aR1 was reportedly shown to confer a considerable level of protection in brain disorders involving neuroinflammatory responses and blood brain barrier disruption (Jacob and Alexander 2014 ). Jiang et al ( 2019 ) reported complement overactivation in macrophages, which resulted in immunopathology with overexpression of caspase-1 and IL-1β levels in the serum, and subsequently, pyroptosis of these cells in a mouse model of MERS-CoV infection (Jiang et al 2019 ). Notwithstanding, treatment with anti-C5aR1 antibody effectively suppressed the expression of caspase-1 and IL-1β, to abrogate the immunopathology and pyroptosis of the macrophages, suggesting that C5a/C5aR1 signalling pathway constitutes a potential target for the treatment of SARS-CoV-2 infection (Jiang et al 2019 ).…”
Section: Neuroimmune Dysregulation By Sars-cov-2 Neuroinvasionmentioning
confidence: 99%
“…The consensus epitope (peptide M) was identified and antiviral properties were established by blocking viral protein expression [ 99 ]. Zhang et al [ 100 ] also reported the potential role of scFvs targeted against viral spike protein to inhibit PEDV infectivity by the plaque reduction neutralization assay and in the prevention and treatment of PEDV infection by oral administration [ 100 ]. Recently a rapid, low-cost, reliable blocking ELISA (bELISA) was developed using phage display technology employing VHH library and biopanning of nanobodies against PEDV N protein [ 70 ].…”
Section: Antibody Selection Against Coronaviruses Using Phage Displaymentioning
confidence: 99%
“…In this study, we observed severe histopathological injury, glial activation, and inflammatory infiltration after CVA6 infection. Increasing evidence suggests that abnormalities cytokines are associated with CNS complications caused by EVA71 and CVA16 infection [ 42 , 43 ]. After EVA71 infection, susceptible cells and nonspecific immune cells are stimulated first to produce cytokines such as TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%